Metode Penyelesaian Hadist Mukhtalif: Kajian Ta'arudh al-Adillah - K Khairuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Hadits position as law postulation to a certain extent provides perplexities to those arguing by. It happens due the existence of bodily contradiction (ta’arudh) among the hadits themselves. Mujtahids (Muslim Scholars) have not reached any agreement on what solution could be applied to reconcile the contradiction. However, the Mujtahids’ method in solving the contradiction can be track through four steps. There are: Al Jam’u wa al-Taufik (talfiq), Nasakh, Tarjih and Tauqif. Author argues that although the scholars have not agreed with those four steps, they have to be applied in a raw. Means that one cannot surpass others. This has to be applied to gain well understanding about a hadist comprehensively.